Detecting Forgery : Forensic Investigation of Documents. - Nickell, Joe (The University Press of Kentucky, 1996)
Detecting Forgery reveals the complete arsenal of forensic techniques used to detect forged handwriting and alterations in documents and to identify the authorship of disputed writings. Joe Nickell looks at famous cases such as Clifford Irving's ""autobiography"" of Howard Hughes and the Mormon papers of document dealer Mark Hoffman, as well as cases involving works of art. Detecting Forgery is a fascinating introduction to the growing field of forensic document examination and forgery detection.